Building Governmental Public Health Capacity to Advance Health Equity: Conclusions Based on an Environmental Scan of a Local Public Health System (Mary Ann Liebert, 2020)
Vast health inequities persist in cities across the United States. Although recommendations exist to guide governmental public health institutions seeking to advance population health equity, local contexts are likely to influence how these pursuits take shape. We review recommendations for pursuing equity that were developed from an environmental scan conducted in the city of New Orleans. The recommendations, which are based on perspectives provided by city and state public health leaders, leaders from other city governmental departments, and community-based health department partners, center around the enduring impact of systemic racism, working across sectors, and prioritizing community engagement.